Aktualʹnye nuždy slovarnoj teorii i praktiki v sovremennoj stilistike - Vinokur, Tatʹâna G. (Stylistyka, 1992)
We can indicate three trends in lexicographical work regarding the stylistic notions: 1) the registration ofthe style’s phenomena in the real linguistic usage and the creation of definitions which would form a terminological system ad hoc; 2) starting from the terminological system existing in particular trend of styles’ research in order to adjust it to the results of an analysis of the linguistic facts; 3) the comparative analisys of various definitions, which is to ensure a sufficiently objective and comprehensive characterization of a style’s phenomenon. The authoress distinguishes among stylistic dictionares: - the dictionares of stylistic tenns (for theoretical stylistics), - the dictionares of style’s means (for practical stylistics).